The impact of selected components of Industry 4.0 on project management - Lukasz Kanski; Jakub Pizon (Journal of Innovation & Knowledge (JIK), 2023)
Purpose Effective project management has contributed to successful operations and process management. The aim of this article is to scrutinize the relationship between a project success and the selected components of Industry 4.0. Instead of being reactive to measuring cost, timeliness, and quality (customer requirements), a more predictive indicator on a project success is needed. Design/methodology/approach The survey involved a group of 370 respondents working in digital (information and communication) technology. The survey questionnaire contained 55 questions focused on 109 features. Data analysis was performed using several statistical techniques . Findings On the basis of a comprehensive survey, the findings show strong possibility for components of Industry 4.0 to be adapted as a predictor of project success, especially for digital upgrade and improvement. Selected components of Industry 4.0 play a key role in assuring effective (and successful) project management. Originality/value The study highlights the impacts from effective project management on industrial and organizational operations. This highlight is based on the attempt to determine whether the components of Industry 4.0 contribute to project success. In this study, in addition to the three traditional factors of cost, timeliness, and quality (or requirements), Industry 4.0 should be considered as a predictor of project management' success. Research limitations/implications The survey was addressed to selected companies operating in the ICT industry (IT projects). The sample selection is based on the non-probability sampling. A novel method of converting respondents' answers into binary form was adopted.
Keywords: 650; ICT projects; Industry; Industry 4.0; Project success